2017
DOI: 10.3390/ijms18112259
|View full text |Cite
|
Sign up to set email alerts
|

Development of A Chimeric Antigen Receptor Targeting C-Type Lectin-Like Molecule-1 for Human Acute Myeloid Leukemia

Abstract: The treatment of patients with acute myeloid leukemia (AML) with targeted immunotherapy is challenged by the heterogeneity of the disease and a lack of tumor-exclusive antigens. Conventional immunotherapy targets for AML such as CD33 and CD123 have been proposed as targets for chimeric antigen receptor (CAR)-engineered T-cells (CAR-T-cells), a therapy that has been highly successful in the treatment of B-cell leukemia and lymphoma. However, CD33 and CD123 are present on hematopoietic stem cells, and targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 28 publications
2
60
0
Order By: Relevance
“…In addition, we have recently shown the relevance of the marker in myelodysplastic syndrome (MDS) and pointed out important differences in the applicability of the marker in these biologically different disease entities (Toft-Petersen et al, 2016). Given this, the CLEC12A receptor is an attractive treatment target in AML, and current developments in this regard include both CLEC12A-CD3 bispecific antibodies (Lu et al, 2014;Leong et al, 2017) and chimeric antigen receptor (CAR)-engineered T-cells (CAR-T-cells) directed against CLEC12A (Laborda et al, 2017;Tashiro et al, 2017;Wang et al, 2018) and, most recently, the development of a novel antibody-drug conjugate (Jiang et al, 2018).…”
Section: Research Papermentioning
confidence: 99%
“…In addition, we have recently shown the relevance of the marker in myelodysplastic syndrome (MDS) and pointed out important differences in the applicability of the marker in these biologically different disease entities (Toft-Petersen et al, 2016). Given this, the CLEC12A receptor is an attractive treatment target in AML, and current developments in this regard include both CLEC12A-CD3 bispecific antibodies (Lu et al, 2014;Leong et al, 2017) and chimeric antigen receptor (CAR)-engineered T-cells (CAR-T-cells) directed against CLEC12A (Laborda et al, 2017;Tashiro et al, 2017;Wang et al, 2018) and, most recently, the development of a novel antibody-drug conjugate (Jiang et al, 2018).…”
Section: Research Papermentioning
confidence: 99%
“…Much the same applies to the developing literature on targeting the CLEC12A receptor (Zhao et al , ; Lu et al , ; Laborda et al , ; Leong et al , ; Tashiro et al , ; Wang et al , ), which has also been shown to be absent on the most immature HSPCs in normal bone marrow (van Rhenen et al , ; Bill et al , ). Recent efforts in targeting this marker include the development of cytotoxic monoclonal antibodies (Zhao et al , ) and CLEC12A‐CD3 bispecific antibodies (Lu et al , ; Leong et al , ).…”
Section: Biological Differences Between Normal Haematopoiesis and Lscmentioning
confidence: 93%
“…A first‐in‐human phase 1 clinical trial of a bispecific CLEC12A‐CD3 antibody for the treatment of relapsed/refractory AML or previously untreated elderly AML patients is currently recruiting (NCT03038230). In addition, the recently developed chimeric antigen receptor (CAR) engineered T cells (CAR‐T cells) directed against CLEC12A (Laborda et al , , Tashiro et al , , Wang et al, ) and toxin‐conjugated antibodies also seem promising (Jiang et al , ). Taken together – and given the success of other antibody‐based initiatives, most prominently rituximab – this line of anti‐LSC targeting is definitely one to follow.…”
Section: Biological Differences Between Normal Haematopoiesis and Lscmentioning
confidence: 99%
“…Efforts to expand adoptive immunotherapy strategies to acute myeloid leukemia (AML) are complicated by antigen overlap between normal hematopoietic progenitor cells (HPCs) and leukemic blasts (8). Early clinical studies of CAR T cells for AML are ongoing, exploring several targets including CD123 (9, 10), CD33 (11), C-type lectin-like molecule 1 (CLL-1) (12,13), and Lewis-Y (14). Additional targets under preclinical investigation include CD135 (FLT-3 receptor) (15)(16)(17), Folate receptor ÎČ (18), CD44v6 (19), WT1 (20), B7-H3 (21-23), CD70 (24,25), and CD7 (26).…”
Section: Introductionmentioning
confidence: 99%